If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -9x = -6x Solving 4 + -9x = -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 4 + -9x + 6x = -6x + 6x Combine like terms: -9x + 6x = -3x 4 + -3x = -6x + 6x Combine like terms: -6x + 6x = 0 4 + -3x = 0 Add '-4' to each side of the equation. 4 + -4 + -3x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = 0 + -4 -3x = 0 + -4 Combine like terms: 0 + -4 = -4 -3x = -4 Divide each side by '-3'. x = 1.333333333 Simplifying x = 1.333333333
| 64^4x=(1/16)^-1-2 | | y=-3E-06x^3 | | 64+r^2=4r^2 | | 12a+24=49 | | 51=b-10 | | 7000=5000+5000(.0425t) | | 4(2+y)-4y=8 | | 3(2x-3)-8=25 | | 4(3x+x)+7-5x=8+(-5x-6x)+23 | | 4n+4+(n+3)=4n+5+2 | | (4d^3/c^3)^3 | | 4x/2=-12 | | 5(2x+7)=5 | | -8=u+2/5-3u+9/2 | | -47+16=4 | | 2(x+5)=3x+7 | | 6x+10x=-8 | | 2cos(5x)=2 | | X=4.2+-0.6y | | 3x-16=104 | | (t+7)(t+9)=0 | | (t+7)(t+9)= | | (3x-16)+104=90 | | (3x-16)+104=180 | | 2(7+(-2y))+12y=30 | | 2x^2-112=0 | | X+2(x+10)+68=x+(x+8) | | x^8+15x^6-36x=0 | | 4n^2-12n+9-p^2=0 | | log(4x+1)=log(x+4)+log(3) | | 2x^2+6x-7=2 | | 5x+x-4=8 |